Preoperative Predictors of Survival After Resection of Small Hepatocellular Carcinomas - Wayne, Jeffrey D. (2002)
OBJECTIVE: To determine preoperative predictors of survival that can guide the choice of treatment for patients with small hepatocellular cancers (HCCs). SUMMARY BACKGROUND DATA: The treatment of patients with small (≤5 cm in diameter) HCCs is controversial. METHODS: A cohort of 249 patients (69 women, 180 men; median age 62 years) who underwent resection with curative intent for small HCC was identified from a multiinstitutional database. For each patient, the clinical data and pathology slides were reviewed. Six clinical factors (age, gender, preoperative α-fetoprotein level, hepatitis serology, number of tumors [single vs. multiple], and Child-Pugh score) and three pathologic factors (hepatitis activity score, fibrosis score, and Edmondson-Steiner tumor grade) that can be determined before surgery were correlated with survival. Log-rank tests and Cox proportional hazards modeling were used to determine factors influencing survival. RESULTS: The median overall survival for the entire cohort was 4.2 years. The estimated overall 5- and 8-year survival rates were 41.1% and 19.8%, respectively. Multivariate Cox analysis indicated that fibrosis score, Edmondson-Steiner grade, and Child-Pugh score were simultaneously significant predictors of survival after resection. A prognostic scoring system based on these covariates was derived and applied to the entire cohort. Patients lacking all three risk factors were assigned a score of 1, patients with one risk factor were assigned a score of 2, and patients with two or three risk factors were assigned a score of 3. Pairwise log-rank tests indicated significant differences in survival between scores 1 and 2, scores 2 and 3, and scores 1 and 3. This scoring system retained its prognostic significance when a subset of 98 patients with positive hepatitis C serology was analyzed separately. CONCLUSIONS: Patients with small HCCs who will derive the least benefit from resection can be identified before surgery using a score based on tumor grade and the severity of underlying liver disease. In these patients, transplantation and/or ablation should be considered as possible alternative therapies.